2021
DOI: 10.3390/molecules26237342
|View full text |Cite
|
Sign up to set email alerts
|

Chlorin e6-Biotin Conjugates for Tumor-Targeting Photodynamic Therapy

Abstract: To improve the tumor-targeting efficacy of photodynamic therapy, biotin was conjugated with chlorin e6 to develop a new tumor-targeting photosensitizer, Ce6-biotin. The Ce6-biotin had good water solubility and low aggregation. The singlet-oxygen generation rate of Ce6-biotin was slightly increased compared to Ce6. Flow cytometry and confocal laser scanning microscopy results confirmed Ce6-biotin had higher binding affinity toward biotin-receptor-positive HeLa human cervical carcinoma cells than its precursor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…LA‐IR820, LA‐SS‐IR820, and LA‐DEG‐IR820 exhibit similar singlet oxygen generation upon 660 nm laser irradiation. The singlet oxygen quantum yields (Ф Δ ) of free IR820, LA‐IR820, LA‐SS‐IR820 and LA‐DEG‐IR820 were determined by using Ce6 as a reference photosensitizer (W. Liu et al, 2021). As shown in Table 2, the Ф Δ of free IR820, LA‐IR820, LA‐SS‐IR820, and LA‐DEG‐IR820 are 0.083, 0.095, 0.084, and 0.082, respectively, indicating that LA‐IR820, LA‐SS‐IR820, and LA‐DEG‐IR820 exhibit similar in vitro photodynamic effect as compared to free IR820.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…LA‐IR820, LA‐SS‐IR820, and LA‐DEG‐IR820 exhibit similar singlet oxygen generation upon 660 nm laser irradiation. The singlet oxygen quantum yields (Ф Δ ) of free IR820, LA‐IR820, LA‐SS‐IR820 and LA‐DEG‐IR820 were determined by using Ce6 as a reference photosensitizer (W. Liu et al, 2021). As shown in Table 2, the Ф Δ of free IR820, LA‐IR820, LA‐SS‐IR820, and LA‐DEG‐IR820 are 0.083, 0.095, 0.084, and 0.082, respectively, indicating that LA‐IR820, LA‐SS‐IR820, and LA‐DEG‐IR820 exhibit similar in vitro photodynamic effect as compared to free IR820.…”
Section: Resultsmentioning
confidence: 99%
“…Singlet oxygen quantum yield of free IR820, LA-IR820, LA-SS-IR820 and LA-DEG-IR820 was calculated by using Ce6 as a reference photosensitizer (Ф Δ = 0.75 in PBS) (W. Liu et al, 2021). For each compound with DPBF, the absorbance at 405 nm versus irradiation time (660 nm, 600 mW/cm 2 ) was fitted with linear model and the slope was calculated.…”
Section: In Vitro Photodynamic Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Free Ce6-treated cells still showed no fluorescence after laser irradiation, while the ROS content was significantly higher in Ce6@MLRN-treated cells, probably due to the efficient cellular uptake and controlled release of Ce6. In addition, it was reported that free Ce6 tends to aggregate and self-quench with a high concentration in solution, which limits its PDT effect and clinical application . Studies have utilized nanoparticles to improve the stability and PDT effect of Ce6, and clinical research proved that the liposomerization of photosensitizers could improve their quality of fluorescence diagnostics and the optimized effect of PDT .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was reported that free Ce6 tends to aggregate and self-quench with a high concentration in solution, which limits its PDT effect and clinical application. 33 Studies have utilized nanoparticles to improve the stability and PDT effect of Ce6, 34 and clinical research proved that the liposomerization of photosensitizers could improve their quality of fluorescence diagnostics and the optimized effect of PDT. 35 Therefore, the encapsulation of liposomes in our study could efficiently improve the stability, intracellular delivery, and PDT effect of Ce6.…”
Section: Cellular Uptake and Pdt Effects Of Mlrnsmentioning
confidence: 99%